Antibiotic Resistance Developed in Klebsiella: A Retrospective Study of the Past 8 Years - Nimra Taseen (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Klebsiella pneumoniae is a Gram-negative, encapsulated bacterium causing a broad range of severe infections, including pneumonia, liver abscess, and UTIs. Its virulence is driven by factors like a hyper-viscous capsule, pili, LPS, and iron carriers. The emergence of multidrug-resistant and hypervirulent strains (MDR-hvKP), especially carbapenem-resistant variants (CR-hvKP), poses a major global health threat. These strains are increasingly linked to hospital outbreaks and community-acquired infections, with rising prevalence in countries like Pakistan. Understanding antibiotic resistance trends is vital for guiding empirical treatment and improving infection control. Objective: To evaluate the antimicrobial resistance patterns of Klebsiella pneumoniae isolates from clinical samples collected over eight years, highlighting trends in resistance and implications for treatment in a tertiary care hospital. Materials and Methods: It is a Retrospective cross-sectional study done in the Department of Microbiology, Fauji Foundation Hospital, Islamabad, from 1st July 2017 to 30th June 2025. The study included inpatients aged 11–80 years from general and specialized wards (e.g., ICU, CCU, Eye, ENT, Burns, etc.) who consented, excluding those under 11, over 80, or visiting OPDs for routine check-ups. Klebsiella pneumoniae isolates obtained from various clinical specimens were subjected to antimicrobial susceptibility testing using the disk diffusion method on Mueller-Hinton agar. Plates were incubated at 35–37°C for 16–18 hours, and zones of inhibition were measured to determine resistance profiles. Data were recorded, digitized using Microsoft Excel, and analyzed using SPSS version 28.0. Chi-square tests were applied. Results: High resistance rates were observed against third-generation cephalosporins: Cefotaxime (82%), Ceftriaxone (79%), and Ceftazidime (77%), indicating widespread ESBL production. Ciprofloxacin resistance was noted in 74% of isolates. Alarmingly, carbapenem resistance was found in 48% of isolates against Imipenem and 44% against Meropenem, demonstrating the emergence of carbapenem-resistant Klebsiella pneumoniae (CRKP). Amikacin (22% resistance) and Colistin (16% resistance) showed the highest susceptibility but remain at risk of reduced effectiveness. Conclusion: The study highlights a significant increase in multidrug-resistant and hypervirulent Klebsiella pneumoniae strains, necessitating urgent implementation of antimicrobial stewardship, regular susceptibility testing, and molecular surveillance to prevent treatment failures and hospital outbreaks. Keywords: Klebsiella pneumoniae, ESBL, carbapenem resistance, susceptibility testing.